Co-assemblies of carboxymethyl cellulose and wheat glutenins as colloidal carriers of vitamin D3 with enhanced stability against long-term storage and ultraviolet radiation. (February 2023) - Li, Xuyuan; Zhang, Sihan; Luo, Xiaohu; Wang, Ren; Feng, Wei; Zhang, Hao; Chen, Zhengxing; Wang, Tao
Abstract: In this study, carboxymethyl cellulose (CMC) and wheat glutenins (WGs) formed complex structures (CWs) featuring nanoparticles (∼160 nm) fixed at the junctions of fibril networks (50 nm in thickness) with numerous smaller nanoparticles attached to the fibril trunks. The complexation was performed by dissolving CMC and WGs in an alkaline solution (pH 12.0) followed by neutralization. Fluorescence study and Fourier transform infrared spectroscopy indicated that electrostatic forces initiated the binding of WGs to CMC, while hydrophobic attractions contributed to the growth of WG nanoparticles on CMC fibrils. This enabled sufficient dispersing of WGs that can be harnessed as binding sites for vitamin D3 (VD3 ). Importantly, the microstructures of CWs can be delicately controlled by the substitution degree (DS) of carboxymethyls. Consequently, the stability of VD3 against long-term storage and UV radiation by CWs was improved by 77.87–92.55% and 113.13–166.45%, respectively, which were highly dependent on DS. Furthermore, the CWs can realize sustained release of VD3 in simulated gastrointestinal fluid controlled by varied DS. This study provided a facile and effective approach for advanced utilization of WGs with potential applications in the development of novel food structures and formulation of functional ingredients. Graphical abstract: Image 1 Highlights: Particle-on-fibril nanostructures (CWs) were formed by proteins and polysaccharides. VD3 loaded in CWs had enhanced stability against long-term storage and UV radiation. VD3 release can be controlled by carboxymethyl degree of polysaccharides.